2007
DOI: 10.1097/bot.0b013e318148c665
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Reliability of the Hawkins Sign in Fractures of the Talus

Abstract: The Hawkins sign is a good indicator of talus vascularity following fracture. If a full or partial positive Hawkins sign is detected, it is unlikely that AVN will develop at a later stage after injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 15 publications
2
44
0
3
Order By: Relevance
“…Its occurrence predictably rules out avascular necrosis of the talus. 15 In all three of our patients, the talus attached only by a thin friable thread of soft tissue was copiously irrigated with saline prior to reimplantation. Of these, two patients had no evidence of AVN even after two years after the surgery (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Its occurrence predictably rules out avascular necrosis of the talus. 15 In all three of our patients, the talus attached only by a thin friable thread of soft tissue was copiously irrigated with saline prior to reimplantation. Of these, two patients had no evidence of AVN even after two years after the surgery (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Arthritis in the ankle and subtalar joints can occur in the absence of avascular necrosis of the talus and joint incongruity [6,16]. The reported incidence of avascular necrosis for severely comminuted talar body fracture is around 50%-75% [5,10,12,[20][21][22]. Vallier et al reporting on radiographic findings of 26 talar body fractures with a minimum follow-up of 1 year, noted a 38% incidence of AVN, 65% incidence of post-traumatic tibiotalar arthritis and 34% incidence of posttraumatic subtalar arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Canale and Kelly confirmed the utility of the sign but noted that the absence of subchondral atrophy was not a universally reliable indicator of the development of AVN [2]. Tezval et al [16] reviewed 41 patients with talus fractures and found the Hawkins sign to have 100% sensitivity for talar viability; however, the specificity of the sign to rule out the possibility of talar AVN was limited-only 57.7% [16]. In 2014, Chen et al [3] found the Hawkins sign to be a reliable predictor of AVN development and suggested that MRI at 12 weeks might be valuable to identify early AVN in patients who have a negative Hawkins sign.…”
Section: Limitationsmentioning
confidence: 99%